Ammonium Alleviates Manganese Toxicity and Accumulation in Rice by Down-Regulating the Transporter Gene OsNramp5 Through Rhizosphere Acidification - Hu, An Yong; Zheng, Man Man; Sun, Li Ming; Zhao, Xue Qiang; Shen, Ren Fang (Frontiers in Plant Science, 2019)
Ammonium (NH4+) alleviates manganese (Mn) toxicity in various plant species, but the underlying mechanisms are still unclear. In this study, we compared the effects of NH4+ and nitrate (NO3) on rice (Oryza sativa L.) growth, accumulation and distribution of Mn, accumulation of iron (Fe), zinc (Zn) and copper (Cu), root cell wall components and expression of Mn and Fe transporter genes. After rice seedlings were grown in non-pH-buffered nutrient solution for 2 days, the pH of growth medium changed from an initial value of 4.5 to 3.5 and to 5.5 in the presence of NH4+ and in the presence of NO3, respectively. Compared with NO3, ammonium decreased nutrient-solution pH and alleviated Mn toxicity and accumulation in rice under non-pH-buffered conditions. This alleviation disappeared when 5 mM Homo-PIPES pH buffer was added. Regardless of N form, roots, shoots, root cell sap and xylem sap accumulated much lower Mn at pH 3.5 than at pH 5.5, whereas Mn distribution in different leaves and Mn accumulation in root cell walls was affected by neither N form nor pH. Ammonium decreased the expression of the Mn influx transporter gene OsNramp5 in roots under non-pH-buffered conditions, but not under pH-buffered ones. OsNramp5 expression was down-regulated at pH 3.5 compared with pH 5.5. Another efflux Mn transporter gene, OsMTP9, was not regulated by either N form or pH. High pH (5.5) enhanced the expression of the Fe transporter gene OsIRT1 and increased the accumulation of Zn but not Fe or Cu in shoots compared with pH 3.5. Taken together, our results indicate that NH4+ alleviates Mn toxicity and accumulation in rice through the down-regulatory effects of rhizosphere acidification on the Mn influx transporter gene OsNramp5. In addition, the up-regulation of OsIRT1 expression may contribute to the increased Zn uptake by rice at high pH of nutrient solution.